Analisis Efektivitas dan Efisiensi Pajak Reklame serta Kontribusinya terhadap Pendapatan Asli Daerah Kabupaten Buleleng Tahun 2019-2021 - I Putu Gede Diatmika; Ratna Sari, Sang Ayu Made (Universitas Pendidikan Ganesha, 2022)
This study intended to know the level of effectiveness and efficiency of billboard tax collection and its contribution to local revenue of Buleleng Regency in 2019-2021. This descriptive research with a quantitative approach used primary data and secondary data. The data were collected by using observation techniques, interviews and documentation. The data analysis used were effectiveness analysis, efficiency analysis, and contribution analysis. Based on the results, it shows that: 1. The effectiveness of collecting billboard taxes in Buleleng Regency in 2019-2021 tends to increase by 78.87% for 2019 which is classified as less effective; 124.18% for 2020 and 102.26% for 2021 which are classified as very effective, 2. The efficiency of billing advertisement tax collection in Buleleng Regency in 2019-2021 is classified as very efficient with a percentage of 1.34% in 2019; 0.72% in 2020 and 0.32% in 2021, 3. The contribution of the advertisement tax to Buleleng Regency's original revenue in 2019-2021 is classified as very low with a percentage of 0.52% for 2019; 0.61% for 2020 and 0.70% for 2021.